Management of Immune-Related Adverse Events in Patients Treated With Chimeric Antigen Receptor T-Cell Therapy: ASCO Guideline. Issue 35 (10th December 2021) - Santomasso, Bianca D.; Nastoupil, Loretta J.; Adkins, Sherry; Lacchetti, Christina; Schneider, Bryan J.; Anadkat, Milan; Atkins, Michael B.; Brassil, Kelly J.; Caterino, Jeffrey M.; Chau, Ian; Davies, Marianne J.; Ernstoff, Marc S.; et al.
Abstract : PURPOSE: To increase awareness, outline strategies, and offer guidance on the recommended management of immune-related adverse events (irAEs) in patients treated with chimeric antigen receptor (CAR) T-cell therapy. METHODS: A multidisciplinary panel of medical oncology, neurology, hematology, emergency medicine, nursing, trialists, and advocacy experts was convened to develop the guideline. Guideline development involved a systematic literature review and an informal consensus process. The systematic review focused on evidence published from 2017 to 2021. RESULTS: The systematic review identified 35 eligible publications. Because of the paucity of high-quality evidence, recommendations are based on expert consensus. RECOMMENDATIONS: The multidisciplinary team issued recommendations to aid in the recognition, workup, evaluation, and management of the most common CAR T-cell–related toxicities, including cytokine release syndrome, immune effector cell–associated neurotoxicity syndrome, B-cell aplasia, cytopenias, and infections. Management of short-term toxicities associated with CAR T cells begins with supportive care for most patients, but may require pharmacologic interventions for those without adequate response. Management of patients with prolonged or severe CAR T-cell–associated cytokine release syndrome includes treatment with tocilizumab with or without a corticosteroid. On the basis of the potential for rapid decline, patients with moderate to severe immune effector cell–associated neurotoxicity syndrome should be managed with corticosteroids and supportive care. Additional information is available at www.asco.org/supportive-care-guidelines .